Molecular epidemiology ofBordetella pertussisin Greece, 2010‐2015. Issue 3 (March 2018) - Petridou, Evangelia; Jensen, Christel Barker; Arvanitidis, Athanasios; Giannaki‐Psinaki, Maria; Michos, Athanasios; Krogfelt, Karen Angeliki; Petersen, Randi Føns
Abstract : Purpose. : To determine the predominant strains of Bordetella pertussis in Greece during 2010‐2015. Methodology. : Infants and children ( n =1150) (15 days to 14 years) of Greek, Roma and immigrant origin with different vaccination statuses were hospitalized in Athens, Greece with suspected pertussis infection. IS 481 /IS 1001 real‐time PCR confirmed Bordetella spp./ B. pertussis infection in 300 samples. A subset of samples ( n =153) were analysed by multi‐locus variable number tandem repeat analysis (MLVA) and ( n =25) by sequence‐based typing of the toxin promotor region ( ptxP ) on DNA extracted from clinical specimens. Results/Key findings. : A complete MLVA profile was determined in 66 out of 153 samples; the B. pertussis MLVA type 27 ( n =55) was the dominant genotype and all tested samples ( n =25) expressed the ptxP3 genotype. The vaccine coverage in the Greek population was 90 %; however, the study population expressed complete coverage in 2 out of 264 infants (0‐11 months) and in 20 out of 36 children (1‐14 years). Roma and immigrant minorities represent 7 % of the Greek population, but make up 50 % of the study population, indicating a low vaccine coverage among these groups. Conclusions. : The B. pertussis MT27 and ptxP3 genotype is dominant in Greek, Roma and immigrant infants and children hospitalized in Greece. Thus, the predominant MLVA genotype in Greece is similar to other countries using acellular vaccines.